Some Considerations in Accounting for Divisive Reorganizations. - Lembke, Valdean C. (The Accounting Review, 1970)
Abstract The article examines the desirability of the existing practices in accountancy for business combinations to determine the accounting problems that arises when a business separation occurs. The primary issue in accounting for divisive reorganizations centers on the propriety of carrying forward the existing basis of accountability for those assets transferred to the new entity versus creation of a new basis of accountability. Since continuity of ownership in the aggregate is maintained in all divisive reorganizations, it could be argued that all are reverse poolings. An aggregate view of ownership, however, fails to differentiate between those divestitures in which there is a division of the firm between owners and those in which ownership is unaltered. In the context of accounting theory there does not appear to be a body of rationale which clearly disproves the validity of either reverse pooling or reverse purchase treatment. It has been argued by those supporting purchase treatment that business combinations are basically exchange transactions bargained between independent entities.